Volunteer tourism for Muslim community development: applying social exchange theory for cross culture benefits / Nik Rozilaini Wan Mohamed … [et al.] (2015)
This research explores a new phenomenon of alternative tourism known as volunteer tourism. Volunteer tourism is aimed at encouraging youth actively involved in volunteer activities and creates awareness and the role of voluntary accreditation as part of self-development. Volunteers help promote tourism social needs, promote and improve the social network awareness among volunteers. This research investigate how local Muslim communities perceived degree of benefits and costs of volunteer tourism at local Muslim tourism destination, to what extent they will get cross culture benefits from the activities and what level of eco-centric attitude among communities. Local Muslim participants were interviewed to get some information on various components which consists of trusts in tourism institutions, the power of influences, perceived benefits for volunteer tourism, perceived costs for volunteer tourism and local eco centric attitudes. Subsequently the data was analyzed using thematic analysis to transforms the data into findings. Throughout the research, several measurements have taken to address methodologies issues and limitations that result from the approach adopted in Perhentian Island Malaysia.